2013
DOI: 10.1292/jvms.13-0360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Toxoplasma gondii</i> Infection in Rabbits of Korea by Serological Tests and Nested Polymerase Chain Reaction

Abstract: ABSTRACT>This study surveyed the Toxoplasma (T.) gondii infection prevalence in the Korean rabbit population. Rabbits (n=142) were obtained from two breeding farms in the Gongju area, Chungnam Province, and in the Kochang area, Junbuk Province, Korea. Of 142 sera samples analyzed by enzyme-linked immunosorbent assay (ELISA), 15 (10.6%) exhibited T. gondii-specific IgG antibodies, and 1 (0.7%) rabbit harbored T. gondii-specific IgM. Female rabbits (9/84; 10.7%) had a similar T. gondii prevalence to males (6/58;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…These results indicate that there may be a potential association between the breed of rabbits and the seropositivity against T. gondii and E. cuniculi . Most epidemiological surveys indicated no association between T. gondii and E. cuniculi infection and gender of the animals [ 13 , 18 , 19 ]. In our study, the gender of rabbits was not a significant risk factor for the presence of infection with T. gondii , which was in agreement with many previous studies [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that there may be a potential association between the breed of rabbits and the seropositivity against T. gondii and E. cuniculi . Most epidemiological surveys indicated no association between T. gondii and E. cuniculi infection and gender of the animals [ 13 , 18 , 19 ]. In our study, the gender of rabbits was not a significant risk factor for the presence of infection with T. gondii , which was in agreement with many previous studies [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most epidemiological surveys indicated no association between T. gondii and E. cuniculi infection and gender of the animals [ 13 , 18 , 19 ]. In our study, the gender of rabbits was not a significant risk factor for the presence of infection with T. gondii , which was in agreement with many previous studies [ 5 , 18 ]. However, female rabbits exhibited remarkably higher seroprevalence for E. cuniculi in comparison to male animals of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, a similar type of rabbits was surveyed from breeding farms, and 10.6% of them showed T. gondii -specific IgG antibodies [35]. In Egypt, high seroprevalences of T. gondii were also detected, 37.5% and 11.34%, in locally bred and commercial rabbits [3].…”
Section: Discussionmentioning
confidence: 99%
“…The latter study reported fatal toxoplasmosis in three domestic rabbits in the U.S.A. Also, the prevalence of T. gondii in rabbits and its biological circumstances have been emphasized by many epidemiological studies, such as in Spain [1], Egypt [3], Mexico [2], Korea [35] and China [42]. …”
mentioning
confidence: 99%
“…The phylogenetic analysis of 5 B1 gene-positive samples from stray cats showed the highest homology with B1 genes in Indians, American mussels, Thai black rats, and Korean rabbit toxoplasma [34,35]. These strains were all in the same phylogenetic group as the highly pathogenic Type I and moderately pathogenic Type III strain (Type I/III group).…”
Section: B Amentioning
confidence: 94%